(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The COVID-19 pandemic exposed substantial gaps in respiratory care delivery across low-resource regions, where anaesthetists often serve as frontline critical-care physicians. Managing acute respiratory failure in such environments required adapting global recommendations to local realities with limited oxygen infrastructure and ventilatory equipment. This study assessed anaesthetic-led respiratory support strategies and clinical outcomes among patients with severe and critical COVID-19 managed at the Rivers State COVID-19 Treatment Centre, Eleme, Nigeria. A retrospective review of 900 hospitalised COVID-19 cases between March and September 2020 was conducted. After applying exclusion criteria, 305 eligible patients were analysed and classified according to the Nigerian Centre for Disease Control (NCDC) case definitions. Data on demographics, comorbidities, oxygen therapy, non-invasive ventilation (NIV), and outcomes were extracted and statistically analysed. All patients received oxygen therapy as first-line treatment, while 61 (20%) required escalation for persistent hypoxaemia. NIV was successful in 54 (88.5%) of these cases, primarily among younger patients with fewer comorbidities. Seven patients (2.3%) failed NIV and required invasive mechanical ventilation (IMV), all of whom subsequently died. The IMV group was characterised by higher mean age, body mass index, and comorbidity burden, with a mean PaO₂/FiO₂ ratio of 136.3 ± 91.1 mmHg. Early initiation of oxygen therapy and timely NIV markedly reduced the need for intubation and improved overall survival. Effective respiratory management of COVID-19 in low-resource settings depends on early oxygen supplementation, vigilant monitoring, and prompt escalation of non-invasive support. Delayed transition to invasive ventilation remains associated with poor outcomes. Strengthening anaesthesia-led critical-care capacity and oxygen infrastructure is therefore essential to improving survival in future respiratory pandemics.